Análisis estadístico de datos hidrometeorológicos en estudios de erosión acelerada. Un estudio de caso en la cuencua del río Tlalpujahua, México - Gerardo Bocco (Investigaciones Geográficas, 1989)
The statistical analysis of hydrometeorological data is proposed in order to assess the influence of the relationship precipitation/runoff in the development of man-induced gullies. The results allow two logical models of erosion development. In the metamorphics: less antecedent moisture required for runoff to start -quick hydrologic response -superficial flows -gullies. In the volcanics: more antecedent moisture -delayed hydrologic response -soil slumping -gullying in disturbed areas.